Do Remittances Influence Capital Market Development? Evidence from the Nepal Stock Exchange? - Thapa, Krishna Bahadur (DEPAN, 2025)
Remittances are a significant source of income for many developing countries, including Nepal, where they contribute significantly to GDP. These inflows influence household consumption, savings, and further they may impact capital market activities. This study explores how remittances affect stock market performance, focusing on the stock market performance. The aim is to assess both short- and long-run effects of remittances on market growth, liquidity, and investor behavior. Using monthly time series data from June 2010 to July 2024, the study employs a quantitative approach with econometric models, including “co-integration tests, Vector Autoregression (VAR), Wald tests, and Granger causality analysis”. Data were collected from secondary sources such as “the Nepal Stock Exchange, Nepal Rastra Bank, World Bank, and listed companies’ financial reports”. The analysis was conducted using EViews 10. The findings reveal that the optimal lag length is 1. Co-integration tests show no long-term relationship between remittances and the stock market. The VAR model results indicate that remittances have no significant short-run impact on the Nepse index, which is largely influenced by its own previous values. The Wald test approves that remittance lags do not jointly affect the index. Granger causality tests reveal no causal link from remittances to the stock index, though the index. This study adds new understandings to existing literature and provides policy implications for enhancing the role of remittances in Nepalese capital market development.